Manajemen Pembiayaan Sekolah dalam Menambah Sumber Pembiayaan Pendidikan Melalui Wirausaha di Sekolah Dasar Muhammadiyah Bekonang - Nurhidayati, Indah; Sulistyowati (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
The purpose of this study is to know; 1) School Financing Management in increasing sources of education financing through entrepreneurship in Muhammadiyah Bekonang Elementary Schools in 2023 (2) the Results of the strategy to increase sources of education financing through entrepreneurship in Muhammadiyah Bekonang Elementary Schools in 2023. This study used a descriptive qualitative research method. The research was conducted at Muhammadiyah Bekonang Elementary School, in July-August 2023. Subject of study: Principal. Informants: (1) employees (2) committees (3) guardians (4) students. Data collection techniques use observation, interviews, and documentation. The technique of checking the validity of data uses triangulation with sources. Data analysis techniques using interactive methods include data collection, data reduction, data presentation and conclusions. The results of this study; 1) School Financing Management in increasing sources of education financing through entrepreneurship in Muhammadiyah Bekonang Elementary Schools (SD) in 2023 is carried out through: a) Planning for the empowerment of existing resources, namely traders, teachers and employees as managers of entrepreneurs under school management. b) The implementation of the strategy of increasing sources of education financing through entrepreneurship is carried out under school management where sellers are officers and catering suppliers, Teachers and employees as officers and suppliers of healthy canteens, and event organizers targeting other school teachers and the community. c) Evaluation of strategies to increase sources of education financing through entrepreneurship, namely improving communication with parents regarding the order of catering payments, controlling the nominal number of student snacks, and planning event organizers more mature and administrative.2) The results of the strategy to increase sources of education financing through entrepreneurship can increase sources of education financing, especially from catering entrepreneurs, provide healthy consumption for the school community, and improve the quality of schools.